The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/jech-2017-210163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a youth-led social marketing intervention run by adolescents to encourage healthy lifestyles among younger school peers (EYTO-Kids project): a parallel-cluster randomised controlled pilot study

Abstract: BackgroundEncouraging healthy lifestyles in children is a challenge. This project aimed to improve lifestyles of younger peers by engaging adolescent creators (ACs) to design and implement peer-led and social marketing (SM) health-promoting activities.MethodsA 10-month parallel-cluster randomised controlled school-based pilot study was performed in disadvantaged neighbourhoods in Reus (Spain) spanning two academic years (2015–2016/2016–2017). Eight primary schools (n=375 children) and four high schools (n=94AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Improvements in physical activity and fitness behaviors were reported in 12 studies ( 54 , 93 , 96 , 101 , 105 , 126 , 142 , 149 , 161 , 164 , 165 , 169 ), five of these involved an RCT ( 101 , 142 , 164 , 165 , 169 ), seven employed a collaborative ( 54 , 93 , 96 , 105 , 161 , 165 , 169 ) mode of adolescent participation and seven involved a peer-component ( 93 , 96 , 105 , 126 , 149 , 164 , 169 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Improvements in physical activity and fitness behaviors were reported in 12 studies ( 54 , 93 , 96 , 101 , 105 , 126 , 142 , 149 , 161 , 164 , 165 , 169 ), five of these involved an RCT ( 101 , 142 , 164 , 165 , 169 ), seven employed a collaborative ( 54 , 93 , 96 , 105 , 161 , 165 , 169 ) mode of adolescent participation and seven involved a peer-component ( 93 , 96 , 105 , 126 , 149 , 164 , 169 ).…”
Section: Resultsmentioning
confidence: 98%
“…Encouraging changes in dietary behaviors were reported in 17 studies, as an improvement in dietary intake or nutrition behaviors ( 61 , 91 , 96 , 101 , 105 , 112 , 126 , 149 , 161 , 164 , 165 , 169 ), increased fruit ( 93 ) and vegetable consumption ( 121 ), reduced caloric intake ( 99 ), reduction in sugar sweetened beverage intake ( 108 ) or an increase in water consumption ( 54 ). Overall studies involving improvements in dietary behaviors had in common that they were more likely to be collaborative (9/17) ( 54 , 91 , 93 , 96 , 105 , 108 , 161 , 165 , 169 ) and involve a peer-component (10/17) ( 61 , 91 , 93 , 96 , 105 , 108 , 126 , 149 , 164 , 169 ). Studies which reported an improvement in dietary behaviors were almost evenly of qualitative (7/17) ( 54 , 93 , 105 , 112 , 121 , 126 , 149 ) or RCT (6/17) design ( 91 , 101 , 108 , 164 , 165 , 169 ).…”
Section: Resultsmentioning
confidence: 99%
“…The search resulted in 2583 items (see flow diagram in Fig. 1), and identified 30 published papers analysing 15 intervention studies (12 registered RCTs, three pre-post designs) that met the criteria for inclusion in the review (Aittasalo et al 2019;Andrade et al 2014Andrade et al , 2015Babic et al 2016;Babic et al 2015;Bagherniya et al 2018;Barbosa Filho et al 2019;Barbosa Filho et al 2016;Barbosa Filho et al 2015;Cui et al 2012;Foley et al 2017;Hamulka et al 2018;Hankonen et al 2016Hankonen et al , 2017Jussila et al 2015;Leme et al 2016;Leme and Philippi 2015;Lubans et al 2016a;Lubans et al 2016b;Majumdar et al 2013;Singh et al 2006Singh et al , 2009Singh et al , 2007Smith et al 2017;Smith et al 2014aSmith et al , 2014bTarro et al 2017, Tarro et al 2019Vik et al 2015;Wadolowska et al 2019). Out of the 15 studies, eight were analysed in more than one paper, presenting a separate rationale/study protocol or protocol and baseline results and additional effectiveness of RCT papers ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The opposite was found in Manjumdar et al's study (2019), with significant effects for the other intervention objectives (sweetened beverages and snacks) and no changes for ST. Positive intervention effects with increased percentages in those meeting daily recommendations for duration of watching TV and computer use were found in the studies by Barbosa Filho et al (2019) and Tarro et al (2019). The Singh et al (2009) study reported ST reduction for boys 20 months post intervention.…”
Section: Effectivenessmentioning
confidence: 87%
“…This highlights the necessity of supportive school food environment for enabling adolescents to make healthy choices. Promising avenues in this regard range from peer-led nutrition promotion program, school meal program or subsidized canteens serving healthy foods, regulation of food vending within and beyond school boundaries and so forth [79][80][81]. Like the neighboring country India, schools in Bangladesh are yet to define and adopt school food policies, whereas many Western countries have that in place [82].…”
Section: Discussionmentioning
confidence: 99%